Pemanfaatan Quick Response Code Untuk Peningkatan Pelayanan Pelanggan Pada Restoran - Asep Sucipto Indra Sukma; Asep Muhammad Junaedi; Andhika Nove Rezki; Thoyyibah Tanjung (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
QR code which was once a one-dimensional code, is now a two-dimensional code that can store data larger than barcodes by using QR code data. These codes are implemented in various fields in the form of numbers, letters, binary and other character codes. The study also found that usability did not directly affect user interest, and that perceived usefulness did not affect usability as a facilitator. The type of survey used is a qualitative descriptive survey. The results are displayed in the form of an Android-based application that can simplify restaurant ordering systems and services by supporting QR code technology.